KONSEPSI ETIKA DAN MORAL PENDIDIK DALAM PANDANGAN AL-GHAZALI â€œDI MUKA CERMINâ€ JURGEN HABERMAS - M. Misbah (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2012)
Abstract : Mystical ethics established by Al-Ghazali did not distinguish between good-bad and right-wrong. He put it together in a concept of morality or Akhlak. He stated that the source of all goodness and righteousness is not the reason (rational) nor the public, but the revelation of Allah (al-Qurâ€™an). While Habermas explicitly separates good concept and the concept of justice. For him, the question of the goodness is the subjective preferences concerning the ethics/personal choice (regarding the good according to religion, tradition, and certain belief) that is evaluative. While justice is the moral that is universally normative (human rights concerns as a human being). Achievement of universal justice in the midst of a variety of matters kindness (pluralistic) is within a theory of discourse ethics to achieve the universal consensual justice in a democratic society. Key Words: Etich, Teacher, Morality, al-Ghazali, Jurgen Habermas.